ANALISIS PENGHIMPUNAN LEMBAGA AMIL ZAKAT NASIONAL DAN LEMBAGA AMIL ZAKAT DAERAH - Ahmad Syakur; Moch. Zainuddin (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
Various studies show that the development and performance of the collection of Amil Zakat Institutions at the national level in an area is faster than local LAZ, even local LAZ or many regions have decreased collection. This is due to several factors, especially branding and human resources factors. LAZ in National level has a much broader branding and it is known to the public through several media and human resorces factors. National amil zakat on average has better human resources than local LAZ. However, in Jombang district of East Java there is an interesting phenomenon, namely the performance of local LAZ collection in Jombang is not inferior to the gathering of national LAZ representatives (LAZNAS). This research uses a qualitative approach. This qualitative method is used to analyze the collection and development factors of the Zakat Management Organization in three institutions, two representatives of national LAZ namely NU Care LAZISNU and LAZ Yatim Mandiri, and one LAZ in district level, namely LAZ Ummul Quro (LAZUQ). The results of this study are: 1) The collection of the Amil Zakat Institution in Jombang in 2018 based on the report is as follows. The NU Care LAZISNU Association was the largest, followed by LAZ Ummul Quro and followed by LAZ Yatim Mandiri; 2). The collection of Amil Zakat Institutions in Jombang district is strongly influenced by the level of community trust, the extent of the network, partners and amil's motivation. NU Care LAZISNU Jombang is the most trusted by the community because it is based on NU organizations, it has the widest structure and network. LAZ Ummul Quro, although it is only Local LAZ, it has a district scale, but because it has been established for a long time and it has managed to maintain its existence, so in terms of network and partnership it is also relatively broader than Yatim Mandiri. While LAZ Yatim Mandiri is from one side more popular than LAZ Ummul Quro, but from the side of the collection is below it. LAZ Yatim Mandiri's popularity is supported by national media, while in local issues, Yatim Mandiri is still inferior to LAZISNU and LAZ Ummul Quro due to network and partner factors.